2020
DOI: 10.3390/ijms21186650
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiation and Translation Control: A Link to Radiation Hormesis?

Abstract: Protein synthesis, or mRNA translation, is one of the most energy-consuming functions in cells. Translation of mRNA into proteins is thus highly regulated by and integrated with upstream and downstream signaling pathways, dependent on various transacting proteins and cis-acting elements within the substrate mRNAs. Under conditions of stress, such as exposure to ionizing radiation, regulatory mechanisms reprogram protein synthesis to translate mRNAs encoding proteins that ensure proper cellular responses. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 155 publications
0
15
0
1
Order By: Relevance
“…Subclinical tumors that are undetectable on CT have contributed to debate in the recognition of the carcinogenic capacity of IR 1,23 . Multiple studies have described a time interval of 2-7 years from exposure to IR to a diagnosis of cancer, generating uncertainty about the duration of the latent phase between radiation exposure and the development of neoplastic processes 15,34,35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subclinical tumors that are undetectable on CT have contributed to debate in the recognition of the carcinogenic capacity of IR 1,23 . Multiple studies have described a time interval of 2-7 years from exposure to IR to a diagnosis of cancer, generating uncertainty about the duration of the latent phase between radiation exposure and the development of neoplastic processes 15,34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Ionizing radiation (IR) is the energy transported through rays emitted by radioactive material, X-ray emitters, or tomographs. Radiation from alpha and beta particles, X-rays, and gamma rays provokes a biological response due to the ionization of cellular molecules 1 . Depending on the dose and time of radiation exposure, IR increases the risk of developing cancer, as it interacts with DNA, generating mutations and triggering pro-carcinogenic metabolic pathways 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…From a mechanistic point of view, it can be concluded that DDR and DNA repair pathways (p53, ATM and PARP), antioxidant response (Nrf2 pathway), cell survival/apoptotic death pathways, endoplasmic stress response (UPR), immune/inflammatory response (NF-κB pathway autophagy (mitophagy)) and cell cycle regulation (cyclin B1/CDK1 complex) are implicated in adaptive responses [ 244 ] as well as the translational machinery [ 245 ].…”
Section: Ionizing Radiation (Ir) Effects Involving Mitochondriamentioning
confidence: 99%
“…Low dose is generally defined as <100 mGy while low dose rate is <6 mGy/h [ 1 ]. Signalling mechanisms induced by low doses determine responses of cells tissues and organisms [ 2 , 3 , 4 ]. Non-targeted effects (NTE), which include the bystander effect and delayed non-clonal expression of reproductive death, mutation and chromosomal aberrations dominate the response after low doses [ 4 ].…”
Section: Introduction To Low Dose and Non-targeted Radiobiologymentioning
confidence: 99%